Nazariyat al-muwazanah bayna al-manafi' wa-al-madar fi itar al-qanun al-'amm : dirasah muqaranah fi al-nizam al-Islami wa-al-nuzum al-wad'iyah - Mahmud, Muhammad'Abd Rabb al-Nabi Hasanayn (al-Qahirah : Dar al-Salam, 2008)
Egypt ; economic policy; laws and legislation; Islam and economics
Keywords: Law -- Comparative studies; Islamic law -- Comparative studies